Comparison of clotrimazole 1% cream with 50% tea tree oil extract in a cream base for the treatment of tinea corporis/cruris: A randomized controlled trial - Achyut Pokharel; C Yaptinchay; A E Thaebtharm (Nepal Journal of Dermatology, Venereology & Leprology)
Background: Tinea cruris and corporis are common diseases and can be widespread. Estimated lifetime probability of contracting the disease is as high as 10-20%. Dermatophytic infections are one of the three most frequently observed skin diseases among poor communities in tropical countries. Tea tree oil exerts its antifungal activity by altering membrane properties and compromising membrane associated function resulting in clinical improvement and mycological cure of superficial dermatophytes.